Genetic and non-genetic factors affecting dystocia in cattle, Algeria - HOUSSOU Hind; BENSALEM Mounira; BELHOUCHET Hanene; HEZAM Houcemeddine (Genetics & Biodiversity Journal, 2023)
Dystocia or calving difficulties carry a guarded prognosis for life or future fertility in affected females; cattle are considered to be the most affected species having the highest incidence rate of dystocia. In this study, we used two different approaches to identify the causes of dystocia in cattle raised in Souk-Ahras wilaya during the period (2018 - 2020). First, a survey was conducted on 32 farms to collect data. Then, 103 Montbeliard cows’ pelvic were taken. Our findings indicated that the dystocia was greater in the Montbeliard breed (40%) than in the other breeds (P < 0.05). The most common causes of Dystocia reported by vets were narrow pelvic 45%, uterine torsion 31%, uterine inertia 23%, and other causes 1%. The parity number was more frequent in primiparous with a rate of 62% than in multiparous 38% (P < 0.05). Dystocia was significantly more frequent in artificially inseminated (AI) cows than in natural breeding (NB) cows (P < 0.01). The dimensions of the pelvis were the width of the hips (53.85±5.06 cm), the width of the trochanters (47.77±6.05 cm), the width of the ischia (29.81±7.02), the length of the pelvis (54.42±2.29) and the Body Condition Score (2.51±0.46). In general, a significant correlation (P < 0.01) between chest girth and these measurements (Body Condition Score, live weight, hip width, trochanter width) was reported. It was concluded that the most common cause of dystocia in Algeria was mainly due to narrow pelvic or fetal-pelvic disproportion, so the use of pelvimetry will be a routine examination to predict dystocia in cattle.